Influence of Crop Load on the Composition of Free Amino Acids in Organs of Mature 'Valencia' Late [C. Sinensis (L.) Osbeck] Trees During the Growth Cycle - Calot, M. C.; Legaz, Francisco; Martin, Bernardo (International Society of Citriculture, 2024)
Concentration changes of free amino acids in trees with low and high crop load, grown under trickle irrigation were determined at flowering, fruit set, fruit growth, second flush and dormancy. In low crop load trees, only fibrous roots concentrated significantly more amino acids in all stages. In other tree parts the results were inconsistent, although the higher accumulations were more frequent. The results of the three main amino acids of the low versus high crop load trees throughout the cycle were as follows: bark and wood tissues of branches (4-13 mm 0) and fibrous roots accumulated more proline. The reverse was observed in tissues of lateral roots; high asparagine values appeared in flowers and developing fruits, bark and wood tissues (spring flush twigs and lateral roots) and fibrous roots; arginine levels were higher in lateral root tissues and fibrous roots, and lower in reproductive organs, leaves and tissues of branches (<4 mm 0). The bark of woody organs in trees with both crop loads concentrated more proline than the wood in all stages and the same was observed for asparagine in branches (4-13 mm 0) and lateral roots, whereas the arginine accumulation was lower in the bark of twigs and branches. The highest relative concentrations were as follows: proline 78% in old leaves at dormancy, asparagine 57% in flowers, and arginine 29% in branch wood at flowering.